Modified maternal ECG cancellation for portable fetal heart rate monitor. (February 2017) - Tsui, Sheng-Yang; Liu, Chien-Sheng; Lin, Chii-Wann
Abstract: This letter presents an efficient algorithm to detect fetal heart rates based on linear template subtraction (TS) for portable fetal heart rate monitors. After pre-processing, the covariance function windowing is used to eliminate maternal P-waves, maternal T-waves, baseline wander, and to enhance maternal R-waves and fetal R-waves. Next, fetal ECG is extracted by the modified mECG cancellation method which forms a mECG template by projecting an average maternal R-wave as a basis into exponential domains. Finally, fetal R-peaks are detected using a 2-D phase space matrix. The results show that the true positive rate, false discovery rate, and false negative rate of the proposed method are 86.80%, 5.78%, 13.20% respectively, which are better than those of other single-channel fetal ECG template extraction methods. It turns out that the modified template subtraction method has three main advantages. First, the covariance function windowing easily removes baseline wander, maternal P waves and maternal T waves. Second, the modified mECG cancellation model can extract overlapping signals without causing large waveform distortions. Last, both covariance function windowing and the modified mECG cancellation model are efficient and can operate in real time.